Agro-morphological variability of shea populations (Vitellaria paradoxa CF Gaertn) in the Township of Bassila, Benin Republic - SOUBEROU, Kafilatou; AHOTON, ESSÈHOU LÉONARD; EZIN, VINCENT; SEKO, ELIASSOU (My University, 2016)
Shea (Vitellaria paradoxa CF Gaertn) is a multipurpose forest tree species. This is one of the most integrated species in the cropping systems in the central and northern regions of Benin. It is also an important source of income for the population. Observations were made on some shea trees randomly selected in three vegetation types namely forests, fallows and farms. Data collection on quantitative and qualitative parameters such as length and width of leaves and fruits, tree diameter, fruit shape, crown shape, shape of leaf apex were made on 90 shea trees. The results show that the average density of shea trees per hectare varies (not significantly different) according to the three vegetation types (farms, fallow, and forests). The average diameter of tree trunk at man chest level was 37.35 ± 7.78 cm with a coefficient of variation (CV) within population was 21.09%. Variations between Shea populations in the study area were quite important and show the diversity of natural populations of the species. Leaves were predominantly oblong shape with an average length of 18.33 ± 3.21 cm and an average width of 6.92 cm ± 1.28; the leaf apex was in “pointed” shape. The fruits were dominantly oblong in the three vegetation types. The fruits had an average length of 4.49 ± 0.77 cm and a mean diameter of 3.56 ± 0.48 cm. The crown in shape of broom was observed so frequently in the different vegetation types. The longest and widest leaves and the longest and largest fruits were found in fields and fallows, while the smallest leaves and fruits were found in the forests.
Keywords: Vegetation types; Vitellaria paradoxa; morphological diversity; Benin